Factors influencing voluntary tax compliance of self-employed individuals in Davao city - Maquiling, Rebecca; Manolong, Denise Lea Jean O; Naong, Twinkle M; Sumaylo, Michea Gaye C (Technium Business and Management, 2023)
Most self-employed taxpayers, who are exempted from third-party reporting, is being evaded. Compared to employees and corporations, self-employed have a low percentage of compliance due to government regulation focusing more on large taxpayers, resulting in fiscal imbalance. Thus, this study aims to determine the significant influence of the tax behavior factors on the tax compliance status of self-employed individuals in Davao City. The study uses descriptive-correlational method and adapted a modified questionnaire to collect data from 180 self-employed taxpayers. Findings reveal that the level of four indicators: personal, institutional, economic, and social are high than the expected level. It also shows that the level of tax compliance in terms of administration and submitting tax returns are found to be tax compliant most of the time. Using the multiple regression analysis, only institutional and social factors significantly influence tax compliance. It is recommended that the government should further strengthen the tax authority's efficiency and effectiveness while making the tax system equitable. The researchers also suggest tax forms must be convenient and tax structure must be fair and just to likely increase the number of tax returns and ensure the favorable attitude of self-employed individuals towards taxation.